Spatial analysis for Piper species distribution in India - Parthasarathy, U.=700 1 Gworge, J.; Saji, K.V.; Srinivasan, V.; Madan, M.S.; Mathur, P.N.
(En, Fr, Es)
Ilus., 5 ref.
Keywords: PIPER; DISTRIBUCION GEOGRAFICA; SISTEMAS DE INFORMACION GEOGRAFICA; INDIA; PIMIENTA NEGRA